Deglaciation of the Laurentide Ice Sheet from the Last Glacial Maximum - Ch.R. Stokes (Cuadernos de Investigación Geográfica, 2017)
The last deglaciation of the Laurentide Ice Sheet (LIS) was associated with major reorganisations in the ocean-climate system and its retreat also represents a valuable analogue for understanding the rates and mechanisms of ice sheet collapse. This paper reviews the characteristics of the LIS at its Last Glacial Maximum (LGM) and its subsequent deglaciation, with particular emphasis on the pattern and timing of ice margin recession and the driving mechanisms of retreat. The LIS initiated over the eastern Canadian Arctic ~116-110 ka (MIS 5d), but its growth towards the LGM was highly non-linear and punctuated by several episodes of expansion (~65 ka: MIS 4) and retreat (~50-40 ka: MIS 3). It attained its maximum position around 26-25 ka (MIS 2) and existed for several thousand years as an extensive ice sheet with major domes over Keewatin, Foxe Basin and northern Quebec/Labrador. It extended to the edge of the continental shelf at its marine margins and likely stored a sea-level equivalent of around 50 m and with a maximum ice surface ~3,000 m above present sea-level. Retreat from its maximum was triggered by an increase in boreal summer insolation, but areal shrinkage was initially slow and the net surface mass balance was positive, indicating that ice streams likely played an important role in reducing the ice sheet volume, if not its extent, via calving at marine margins. Between ~16 and ~13 ka, the ice sheet margin retreated more rapidly, particularly in the south and west, whereas the north and east underwent only minimal recession. The overall rate of retreat decreased during the Younger Dryas (YD), when several localised readvances occurred. Following the YD, the ice sheet retreated two to five times faster than previously, and this was primarily driven by enhanced surface melting while ice streams reduced in effectiveness. Final deglaciation of the Keewatin and Foxe Domes, left a remnant Labrador Dome that disappeared ~6.7 ka.